Safer-by-design biocides made of tri-thiol bridged silver nanoparticle assemblies. Issue 3 (11th November 2019) - Marchioni, Marianne; Veronesi, Giulia; Worms, Isabelle; Ling, Wai Li; Gallon, Thomas; Leonard, Didier; Gateau, Christelle; Chevallet, Mireille; Jouneau, Pierre-Henri; Carlini, Laura; Battocchio, Chiara; Delangle, Pascale; et al.
Abstract : A tri-thiol bio-inspired ligand triggers thiol-mediated silver nanoparticle assemblies. This novel nanomaterial delivers an amount of Ag(i ) sufficient for biocidal activity but no release of AgNPs that makes it a safer solution for future applications. Abstract : Silver nanoparticles (AgNPs) are efficient biocides increasingly used in consumer products and medical devices. Their activity is due to their capacity to release bioavailable Ag(i ) ions making them long-lasting biocides but AgNPs themselves are usually easily released from the product. Besides, AgNPs are highly sensitive to various chemical environments that triggers their transformation, decreasing their activity. Altogether, widespread use of AgNPs leads to bacterial resistance and safety concerns for humans and the environment. There is thus a crucial need for improvement. Herein, a proof of concept for a novel biocide based on AgNP assemblies bridged together by a tri-thiol bioinspired ligand is presented. The final nanomaterial is stable and less sensitive to chemical environments with AgNPs completely covered by organic molecules tightly bound via their thiol functions. Therefore, these AgNP assemblies can be considered as safer-by-design and innovative biocides, since they deliver a sufficient amount of Ag(i ) for biocidal activity with no release of AgNPs, which are insensitive to transformations in the nanomaterial.